Meneropong Kinerja Pekerja Sosial dalam Pelayanan Rehabilitasi Pengguna NAPZA di Klinik Rehabilitasi Medan Plus - Dea Alya; Gebi Margareta; Maria Marsella; Natasya Bintang; Fajar Utama Ritonga (Lembaga Pengembangan Kinerja Dosen, 2025)
Drug abuse is a social problem that has a wide impact on the psychosocial conditions of individuals and society. One of the efforts to overcome it is through rehabilitation, where social workers have an important role in assisting the recovery process of drug users. This study aims to describe the role of social workers in assisting clients in rehabilitation centers. The study used a qualitative approach with data collection techniques in the form of in-depth interviews and direct observation of assistance activities at the Medan Plus Drug Rehabilitation Foundation. The results of the study showed that social workers play a role in conducting assessments, designing intervention plans, providing individual and group counseling, and assisting the client's social reintegration process. The presence of social workers has been proven to be able to support client recovery in a sustainable manner, both in terms of emotional, social, and preparation for returning to society. This finding emphasizes the importance of optimizing the role of social workers in organizing rehabilitation services so that the client's recovery process becomes more effective and sustainable.